(3YhGFO GdCjGe aj HjGf bhGYO GdCMcGes - (3GdcGTGfj, GdRGbj, CMeO Hf eMeO egOj Hf CHj PqQ, J (B1244 (3g`s
(3ChdgG (B:s
(3HSe Gddg(B...(3GdMeO ddg Ydi eG CfYe hGdTcQ Ydi eG Cdge hGdUdGI Ydi HGYK CeLGO GdYGde eMeO SjO GdYQH hGdYLe(B...(3gPG eG GSJWQaJg ef YhGFO GdCjGe ef egeGJ COdI GdCMcGe hcdjGJ eSGFd GdMdGd hGdMQGe(B...s
(3BNQgG (B:s
...(3aEf MUd dg efgG GdXf adjbd HMLjJgG hEdG adG, hefge ef jbhd HMLjI cd NHQ ZjQ eYdhe GdcPH(B...(3hGddg CYde HMbjbI GdMGd(B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B1(3,U(B269s
(3eYLe GdeDdajf(B:(3L(B1(3,U(B313s
(3EjVGM Gdecfhf(B:(3L(B2(3,U(B130s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis